2008
DOI: 10.1007/s11325-008-0169-7
|View full text |Cite
|
Sign up to set email alerts
|

Low-grade urinary albumin excretion in normotensive/non-diabetic obstructive sleep apnea patients

Abstract: Previous studies have indicated that high levels of urinary albumin excretion (UAE) are associated with an increased incidence of cardiovascular morbidity and mortality. This study examined the association between UAE and obstructive sleep apnea syndrome (OSAS). The study included 35 newly diagnosed OSAS patients and 11 nonapneic controls. Subjects with diabetes mellitus, hypertension, a history of renal failure, cardiac failure, coronary heart disease, collagen tissue disease, high serum creatinine, and urina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 28 publications
(36 reference statements)
1
11
1
Order By: Relevance
“…A cross-sectional study showed nondiabetic adults with untreated hypertension to have significantly greater ACR (by 57%) in the presence of OSA that correlated with AHI and 24-hour pulse pressure [20]. A case-control study showed low-grade albuminuria in nondiabetic normotensive adults with OSA that correlated with length of time at oxygen saturation <90% and BMI [21]. Our findings do not agree with these studies, which is likely due to our study design.…”
Section: Discussioncontrasting
confidence: 73%
“…A cross-sectional study showed nondiabetic adults with untreated hypertension to have significantly greater ACR (by 57%) in the presence of OSA that correlated with AHI and 24-hour pulse pressure [20]. A case-control study showed low-grade albuminuria in nondiabetic normotensive adults with OSA that correlated with length of time at oxygen saturation <90% and BMI [21]. Our findings do not agree with these studies, which is likely due to our study design.…”
Section: Discussioncontrasting
confidence: 73%
“…A further 19 articles were excluded following detailed review, of which 3 were review articles, which we reviewed to find potential relevant articles [ 10 , 12 , 18 ]. The remaining 16 were excluded for the following reasons: 1 focused on central apnea [ 19 ], 6 did not have a clear definition of nephropathy [ 20 25 ], 3 may have contained biased data (e.g., 1 related to creatinine clearance, i.e., over 200 ml/min [ 26 ], 2 had fewer than 10 subgroup participants [ 27 , 28 ]), 3 had missing data [ 6 , 7 , 29 ], and 1 focused only on the OSA population without a control group [ 30 ]. Finally, 18 studies [ 5 , 8 , 9 , 31 – 45 ] that included 7090 patients were incorporated in our meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have shown that urinary albumin-creatinine ratio is an independent risk factor associated with the severity of OSA [54][55][56] . Faulx et al [54] have shown that the severity of OSA is significantly associated with increased urine albumin excretion.…”
Section: Osa and Proteinuriamentioning
confidence: 99%